Manajemen Pelayanan Ibadah Haji pada Masa Pandemi Covid 19 di PLHUT Kantor Kementerian Agama Kabupaten Majalengka - Nurhamidah, Ai; Machendrawaty, Nanih; Setiawan, Asep Iwan (Tadbir: Jurnal Manajemen Dakwah, 2022)
This study aims to determine the planning of Hajj services at the PLHUT of the Office of the Ministry of Religion of Majalengka Regency, to find out the organization of Hajj servicew at the PLHUT pf the Office of the Ministry of Religion of Majalengka Regency and to determine the implementation and evaluation of Hajj services at the PLHUT of the Office of the Ministry of Religion of Majalengka Regency. This research uses case study method and field research. So the results of the research researchers found that the Hajj Service Post (Posyanji) wich provides excellent services which is located in every sub-district so that it becomes an extention of the Ministry of Religion.